2020
DOI: 10.1101/2020.02.19.20025452
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The serial interval of COVID-19 from publicly reported confirmed cases

Abstract: As a novel coronavirus continues to emerge throughout China and threaten the globe, its transmission characteristics remain uncertain. Here, we analyze the serial . CC-BY-NC-ND 4.0 International license It is made available under a is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity. (which was not peer-reviewed)The copyright holder for this preprint . https://doi.org/10. 1101 intervals-the time period between the onset of symptoms in an index (infector) case and the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
124
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(131 citation statements)
references
References 16 publications
5
124
1
Order By: Relevance
“…In order to investigate the variation of with respect to the serial interval, we carry out a sensitivity analysis by changing the mean of the serial interval from 4 to 8 days, the standard deviation (Std) from 3 to 5. The sensitivity analysis is reported in Table 2, and we notice that increases when the mean of the serial interval increases and we remark that serial interval examined by recent studies is shorter than that earlier estimation [22][23][24] . It also follows from Table 2 that increasing Std of the serial interval only slightly decreases the estimated for a given mean of the serial interval.…”
Section: Model-free Estimation For Andmentioning
confidence: 69%
“…In order to investigate the variation of with respect to the serial interval, we carry out a sensitivity analysis by changing the mean of the serial interval from 4 to 8 days, the standard deviation (Std) from 3 to 5. The sensitivity analysis is reported in Table 2, and we notice that increases when the mean of the serial interval increases and we remark that serial interval examined by recent studies is shorter than that earlier estimation [22][23][24] . It also follows from Table 2 that increasing Std of the serial interval only slightly decreases the estimated for a given mean of the serial interval.…”
Section: Model-free Estimation For Andmentioning
confidence: 69%
“…We predicted that public health officials would have to identify and quarantine these imported cases within a week of arrival to limit the risk of transmission, with earlier detection of cases being more efficient. Early detection of cases could be critical, given recent studies estimating a shorter serial interval than previously reported, assuming transmission occurs during the asymptomatic period of infection (10,29). As of February 21, there are at least 14 countries that have reported human-tohuman transmission of SARS-CoV-2 (8).…”
Section: Discussionmentioning
confidence: 99%
“…WHO has positioned SARS-CoV-2 as a global pandemic, and asymptomatic patients with SARS-CoV-2 infection gradually appear 3 As the epidemic develops, the proportion of asymptomatic patients is getting higher and higher (up to 19% in the onset after February 1 st , 2020). The mean latency of asymptomatic patients with SARS-CoV-2 infection was prolonged (10.5 days), but the hospital length of stay was shortened (14.3 days).…”
Section: Discussionmentioning
confidence: 99%
“…As of March 15, 2020, China has accumulated 81,048 cases of SARS-CoV-2 infection and a mortality rate of 3.95 %, also, there is a total of 64322 cases expect China, with a mortality rate of 3.51% 1,2 . The proportion of asymptomatic patients has gradually increased 3 . Asymptomatic patients are still highly contagious, paying special attention to the epidemiological characteristics of asymptomatic patients is of great significance for the control of the epidemic.…”
Section: Introductionmentioning
confidence: 99%